Propriedades ópticas da matéria orgânica dissolvida produzida por cultivos axênicos de fitoplâncton de água doce - Zapparoli, Icaro Coloian (2021)
The dissolved organic matter (DOM) is a heterogeneous mixture of molecules with different weight and reactivity that vary spatio-temporally across aquatic ecosystems, and is a key element of biogeochemical cycles. Phytoplankton is a major producer of labile DOM, regulating the quantity and composition of bioavailable DOM pools that support bacterial growth and carbon flow through food webs, standing up as an important, but poorly explored fraction of the DOM pool. The characterization of the optical properties of the fluorescent DOM (FDOM) is a rapid and inexpensive method that provides information about the DOM origin and reactivity. Here, we characterized the DOM produced by freshwater phytoplankton using fluorescence spectroscopy and parallel factor analysis (PARAFAC) in 123 samples from 45 different species grown in axenic cultures. We hypothesized that related species would produce similar compounds, and this could be detected by FDOM signatures. We identify three fluorophore components that were cross validated using the OpenFluor database. The predominant component was characterized as autochthonous of protein origin, and the other two components were identified as non processed terrestrial and processed by microbial activity, respectively. The freshness and humification indexes varied according to the culture’s growth stage, indicating that degradation may occur under the absence of heterotrophic bacteria or UV radiation, but probably due to chemical oxidation. Besides providing a solid database of FDOM produced by freshwater phytoplankton, we show that the FDOM composition is extremely variable among species, within replicated cultures of the same species, and across culture growth stage. We conclude that the FDOM produced by freshwater phytoplankton detected by optical methods does not seem related to phytoplankton phylogenetic structure